Entrepreneurial school dropouts: A model on signalling, education and entrepreneurship - Jens Fredrik Baumgarten Skogstrøm (University of Oslo, Department of Economics, 2012)
I present a theory on the relationship between educational choice and entrepreneurship in a labour market with asymmetric information. The model shows that, in a labour market where education is used as a signalling device, an imperfect relationship between productivity in education and in the labour market can lead to an equilibrium where a fraction of the high-ability individuals choose to quit school and become entrepreneurs. Using a comprehensive set of Norwegian register data, I find that this is prediction is confirmed empirically: Individuals combining low education with high ability have the highest entrepreneurship rates in the population.
Keywords: L26; M13; J24; 330; Entrepreneurship; self-employment; education; ability; Unternehmensgründung; Unternehmer; Bildungsverhalten; Humankapital; Signalling; Norwegen